Incremental Hospital Cost and Length-of-Stay Associated With Treating Adverse Events Among Medicare Beneficiaries Undergoing Lumbar Spinal Fusion During Fiscal Year 2013. Issue 20 (15th October 2016) - Culler, Steven D.; Jevsevar, David S.; Shea, Kevin G.; McGuire, Kevin J.; Schlosser, Michael; Wright, Kimberly K.; Simon, April W.
Abstract : Supplemental Digital Content is available in the text Abstract : Study Design: A retrospective study. Objectives: To report the incremental hospital resource consumption associated with treating selected adverse events experienced by Medicare beneficiaries undergoing a two- or three-level lumbar spinal fusion. Summary of Background Data: Hospitals are increasingly at financial risk for the incremental resources consumed in treating patients experiencing adverse events because of public and private third-party payers' efforts to base hospital reimbursement on "pay for performance" measures. However, little is known about average incremental resources consumed in treating patients experiencing adverse events following lumbar spinal fusions. Methods: The 2013 fiscal year Medicare Provider Analysis and Review file was used to identify 83, 658 Medicare beneficiaries who underwent two- or three vertebrae-level lumbar spinal fusion. International Classification of Diseases-9th—Clinical Modification diagnostic and procedure codes were used to identify the frequencies of nine adverse events. This study estimated both the observed and risk-adjusted incremental hospital resources consumed (cost and length of stay [LOS]) in treating Medicare beneficiaries experiencing each adverse event. Results: Overall, 17.7% of Medicare beneficiaries undergoing lumbar spinal fusion experienced at least one of the study's adverse events. Medicare beneficiaries experiencing any complication consumed significantly more hospital resources (incremental cost of $8911) and had longer LOS (incremental stays of 5.7 days). After adjusting for patient demographics and comorbid conditions, incremental cost of treating adverse events ranged from a high of $32, 049 (infection) to a low of $9976 (transfusion). Conclusion: Adverse events frequently occur and add substantially to the hospital resource costs of patients undergoing spinal fusion. Shared decision-making instruments should clearly provide these risk estimates to the patient before surgical consideration. Investment in activities that have been shown to reduce specific adverse events is warranted, and this project may allow health systems to prioritize performance improvement areas. Level of Evidence: 3